1998
DOI: 10.1080/014311698214190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digital Elevation Model resolution on topographic correction of airborne SAR

Abstract: Topography in high relief mountainous areas may mask the signal variation in airborne Synthetic Aperture Radar (SAR) data caused by soil moisture, surface roughness and vegetation. It also a ects the quality of image calibration and registration. Good quality calibration and registration are required for the use of SAR in the estimation of soil water. To address the problem of topographic e ects, the widely available standard 30 m Ö 30 m United States Geological Survey (USGS) Digital Elevation Model ( DEM ) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…AW3D30 is a global Digital Surface Model (DSM) with 30 meters spatial resolution and first released on March 2017 25,28-30 . 9,10,31,32 Previously explained that it is appropriate to use a DEM with a similar grid size as the spatial resolution of the analyzed imagery. In this initial study, three types of DEM with different spatial resolution were analyzed based on their original resolution without prior resampling.…”
Section: Digital Elevation Model (Dem)mentioning
confidence: 99%
“…AW3D30 is a global Digital Surface Model (DSM) with 30 meters spatial resolution and first released on March 2017 25,28-30 . 9,10,31,32 Previously explained that it is appropriate to use a DEM with a similar grid size as the spatial resolution of the analyzed imagery. In this initial study, three types of DEM with different spatial resolution were analyzed based on their original resolution without prior resampling.…”
Section: Digital Elevation Model (Dem)mentioning
confidence: 99%
“…Many studies have shown the effect of DEM resolution on the spatial pattern of terrain attributes (Chang and Tsai, 1991;Wolock and Price, 1994;Zhang and Montgomery, 1994;Gao, 1997;Goyal et al, 1998;Chaplot et al, 2000;Schoorl et al, 2000;Wilson et al, 2000;Thompson et al, 2001;McMaster, 2002). Zhang and Montgomery (1994) used DEM of different resolutions in conjunction with the D8 flow algorithm to detect patterns in storm runoff and surface saturation.…”
Section: Introductionmentioning
confidence: 98%
“…The digital elevation model was used to derive a grid of slope steepness. A 5 × 5 average (smoothing) filter was applied to clean the slope layer from small (suspicious) units (Goyal et al, 1998). The new output grid was converted to polygons to define the slope units.…”
Section: Methodsmentioning
confidence: 99%